Ethnobotanical study on edible flowers in Xishuangbanna, China - Qing Zhang; Zhuo Cheng; Yanxiao Fan; Dezheng Zhang; Miaomiao Wang; Jihai Zhang; Sarana Sommano; Xianjin Wu; Chunlin Long (BMC, 2023)
Abstract Background Edible flowers (EFs) represent valuable sources of both food and medicinal resources, holding the promise to enhance human well-being. Unfortunately, their significance is often overlooked. Ethnobotanical studies on the EFs are lacking in comparison with their botanical and phytochemical research. The practice of consuming flowers as food has a rich culture and long history in China, especially among different linguistic groups in Xishuangbanna, Yunnan. However, economic activities have led to a decline of this tradition. Consequently, preserving the traditional knowledge and culture tied to the EFs in Xishuangbanna becomes both essential and pressing. Methods The field ethnobotanical survey was conducted in Xishuangbanna during five visits in April 2021 and May 2023, covering 48 villages and 19 local markets of all three county-level areas and 9 different linguistic groups. By conducting a comprehensive literature review and on-site field surveys, relevant information regarding the EFs of Xishuangbanna was systematically collected and documented. Additionally, the relative frequency of citation (RFC) values were calculated from the survey data. Results A total of 212 taxa (including species and varieties) of EFs from 58 families and 141 genera were documented in the study area. The edible parts of flowers were classified into 13 categories including peduncle, petal, flower buds, inflorescence as a whole, and etc. They were consumed in 21 ways and as 8 types of food. The inflorescence was the most commonly consumed category, accounting for 85 species (40.1%) of the total categories. They always eat flowers as vegetables (184 species, 86.8%). The preparing form of stir-frying was the preferred food preparation method (138, 65.1%). The Xishuangbanna locals had profound knowledge of which EFs required specific processing to remove their toxicity or bitterness. The dishes can be made from either exclusively from the flowers themselves or by incorporating them alongside other plant parts like stems and leaves. Some EFs with high RFC value, such as Musa acuminata and Bauhinia variegata var. candida, showed significant cultural meanings. These edible flowers occupy specific positions in local traditional culture. Conclusion Traditional knowledge regarding edible flowers holds substantial significance and serves as a representative element of the flower-eating culture in Xishuangbanna. Nevertheless, this knowledge and cultural practice are currently decreasing. Serving as a bridge between tradition and modernity, the flower-eating culture, which derives from local people's practical experience, shows the potential of EFs and can be applied to the conservation of biocultural diversity, healthy food systems, and sustainable development.